Analisis Komparatif Resiko Keuangan BPR Konvensional dan BPR Syariah di Kalimantan Timur - Norma Yuliyanti; Justina Ade Juniardi; Maryam Nadir (Jurnal Ilmu Manajemen Mulawarman (JIMM), 2017)
The Analysis Comparative of financial risk of credit populace bank conventional and credit bank populace syariah in East Borneo (supervised by Mrs Justina Ade Juniardi and Mrs Maryam Nadir).The pupose of this research is to know level of financial risk at credit populace bank conventional and credit populace bank syariah. Sample that use in this research is two credit populace bank use with criteria purposive sampling. Data analysis that use in this research is with Altman Zscore Method.The result of this rresearch show if Â credit bank populace syariah have high financial risk and potentially bankrupt more than credit populace bank conventional.Key Word: Financial Risk, Bankrupt Prediction, Altman ZScore.Â